The Relationship Between Cognitive Jealousy and Stress Levels In Romantic Relationships In Emerging Adulthood - Regina Rahmannisa Retossa; Nurul Wardhani; Wilis Srisayekti (Green Publisher Indonesia, 2024)
This research aims to determine the relationship between cognitive jealousy and stress levels in emerging adulthood individuals who are in romantic relationships. Lazarus & Folkman's theory and Pfeiffer and Wong's theory are used as a framework for understanding how cognitive jealousy can influence stress levels. The research method used is quantitative with a correlational approach. Data was collected through an online survey using an adapted questionnaire of the Multidimensional Jealousy Scale (MJS) and Perceived Stress Scale (PSS). The results of data analysis show that there is a relationship between cognitive jealousy and stress levels in 290 participants. These findings highlight the importance of awareness of the emotional impact of romantic relationships in emerging adulthood individuals. The research results show that there is a significant and directly proportional relationship between cognitive jealousy and stress levels in emerging adults who are in a romantic relationship. This means that the higher the level of cognitive jealousy experienced by emerging adulthood individuals who are in a romantic relationship, the higher the level of stress experienced by the individual.